In vitro inhibition of brain mitochondrial monoamine oxidase by 6-hydroxydopamine. - Youdim, M B (1975)
6-Hydroxydopamine (6-OHDA) inhibits rat brain mitochondrial monoamine oxidase (MAO) when kynuramine or dopamine are used as substrates. The effect is competitive and reversible giving Ki values of 74 and 176 muM with the respective substrates. At high concentrations (5 mM) of each substrate, inhibition of MAO was not observed.